Assessing the abundance of Bristol Bay belugas with genetic mark‐recapture methods. Issue 3 (5th January 2018) - Citta, John J.; O'Corry‐Crowe, Gregory; Quakenbush, Lori T.; Bryan, Anna L.; Ferrer, Tatiana; Olson, Myra J.; Hobbs, Roderick C.; Potgieter, Brooke
Abstract: The Bristol Bay stock of beluga whales ( Delphinapterus leucas ) is genetically distinct and resides in Bristol Bay year‐round. We estimated the abundance of this population using genetic mark‐recapture, whereby genetic markers from skin biopsies, collected between 2002 and 2011, were used to identify individuals. We identified 516 individual belugas in two inner bays, 468 from Kvichak Bay and 48 from Nushagak Bay, and recaptured 75 belugas in separate years. Using a POPAN Jolly‐Seber model, abundance was estimated at 1, 928 belugas (95% CI = 1, 611–2, 337), not including calves, which were not sampled. Most belugas were sampled in Kvichak Bay at a time when belugas are also known to occur in Nushagak Bay. The pattern of genetic recaptures and data from belugas with satellite transmitters suggested that belugas in the two bays regularly mix. Hence, the estimate of abundance likely applies to all belugas within Bristol Bay. Simulations suggested that POPAN estimates of abundance are robust to most forms of emigration, but that emigration causes negative bias in both capture and survival probabilities. Because it is likely that some belugas do not enter the sampling area during sampling, our estimate of abundance is best considered a minimum population size.